Enviromental influence and intention to quit smoking among college students - Zainal Abidin, Muhammad 'Adil; Kadir@Shahar, Hayati; Abdul Manaf, Rosliza (Faculty perubatan dan sains kesihatan UPM, 2019)
Introduction: Secondhand tobacco smoke is a known carcinogen and has shown positive association with smok- ing status, susceptibility and cessation. Smoke free environment policy seem to reduce this exposure and influence intention to quit and frequency of quit attempts. Despite having a smoke free policy, smokers are still exposed to second hand smoke and this might influence their smoking behaviour and cessation. The objective of this study was to examine the association between environmental tobacco smoke exposures with intention to quit smoking among young adults in college with smoke free policy. Methods: Data were drawn from a cluster based randomised controlled trial in 10 government colleges in Selangor. Baseline characteristics of 160 college smokers were mea- sured using adapted questionnaire. Intention to quit was measured using Transtheoretical Model and environmental influence of tobacco smoke exposure. Results: Majority of the smokers were male (99.4%), single (100%), of Malay ethnicity (94.4%) and Muslim (95.6%). Most of them are in pre-contemplation stage where they do not have any intention to quit (65.6%). On environmental influence, at work or college environmental exposure, majority were exposed between 1 to 2 hours (36.9%) and 3 to 8 hours (40.6%). On exposure at home or hostel, majority were exposed between 1 to 4 hours (44.4%) and 5 to 14 hours (21.9%). In terms of friend’s exposures, majority have most of their friends smoking (68.1%). We found no statistically significant association between environmental influence and intention to quit smoking. Conclusion: Although we found no relationship, future research should examine the pathway between environmental influence and smoking behaviour.